2013
DOI: 10.1089/big.2013.0024
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Analytics In Healthcare:Medications as a Predictor of Medical Complexity

Abstract: Children with special healthcare needs (CSHCN) require health and related services that exceed those required by most hospitalized children. A small but growing and important subset of the CSHCN group includes medically complex children (MCCs). MCCs typically have comorbidities and disproportionately consume healthcare resources. To enable strategic planning for the needs of MCCs, simple screens to identify potential MCCs rapidly in a hospital setting are needed. We assessed whether the number of medications u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 27 publications
(26 reference statements)
0
17
0
Order By: Relevance
“…A previous study has reported that T2DM patients with OAD polypharmacy were more likely to have poorer glycemic control compared with those patients without polypharmacy. 23 Although not specific to elderly patients with T2DM, predictive models in health care suggest that the number of medications a patient takes is predictive of medical complexity 24 ; therefore, it is possible that health care providers may intensify current treatment(s) in order to reduce adverse outcomes in medically complex patients, for example, those with polypharmacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study has reported that T2DM patients with OAD polypharmacy were more likely to have poorer glycemic control compared with those patients without polypharmacy. 23 Although not specific to elderly patients with T2DM, predictive models in health care suggest that the number of medications a patient takes is predictive of medical complexity 24 ; therefore, it is possible that health care providers may intensify current treatment(s) in order to reduce adverse outcomes in medically complex patients, for example, those with polypharmacy.…”
Section: Discussionmentioning
confidence: 99%
“…5 Other studies have found that intensification of treatment decreases with increasing age. 5,6,24 Because of the lack of strong evidence that tight glycemic control is beneficial to older patients with T2DM, health care providers may not intensify treatment regimens in these patients. 25 Previous studies have demonstrated that older patients with T2DM had less treatment intensification compared with patients in other age groups.…”
Section: Discussionmentioning
confidence: 99%
“…CCI and PPS have both been shown to be a good measure of patient comorbidity and complexity in many studies [28,[31][32][33][34][35].…”
Section: Estimating Disease Complexity and Validation Of Measuresmentioning
confidence: 99%
“…While some studies have used the Charlson Comorbidity Index (CCI) [28,[31][32][33] and drug burden [34,35] to estimate patient complexity, validity of these measures as an estimate for patient complexity has rarely been established in Asia. In the absence of income data, SES is typically derived from area-based income level from census data [36,37], insurance status [38] or property value [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…The final model was translated into new standard operating procedures, adopted enterprise-wide, and resulted in better patient care with reduced costs. 12 The culture of health care may be our biggest challenge, as it can demonstrate powerful "pushback" against transformative change. Academic medical centers should identify and communicate how they can adopt and incorporate new customer-or patient-focused innovations into their clinical programs.…”
Section: Identification Of Medically Complex Patientsmentioning
confidence: 99%